Leadership Centrality and Corporate Social Ir-Responsibility (CSIR): The Potential Ameliorating Effects of Self and Shared Leadership on CSIR - Pearce, Craig L.; Manz, Charles C. (2011)
Recent scandals involving executive leadership have significantly contributed to the topic of corporate social responsibility (CSR) becoming one of the most important concerns of the management literature in the twenty-first century. The antithesis of CSR is embodied in executive corruption and malfeasance. Unfortunately such things are all too frequent. We view the degree of centrality of leadership, and the primary power motivation of leaders, as key factors that influence the engagement in corruptive leader behavior and consequent corporate social ir-responsibility (CSIR) in organizations. Shared and self-leadership, on the other hand, we introduce as alternatives to traditional top-down centralized views of leadership that can establish needed checks and balances capable of reducing corruptive tendencies. We offer a conceptual model along with several propositions to help guide future research and practice.
Keywords: Corporate social irresponsibility; Leadership; Self-leadership; SHARED leadership; leadership centrality